Teaching Chemical Reactions Through Local Practices: A Contextual Approach for School Education - Devkota, Krishna Maya; Tamrakar, Pratima; Timilsena, Narayan Prasad; Ghimire , Janardan (Educational Journal, 2025)
This study explores the integration of local knowledge into the teaching of chemical reactions in school education. The research aims to explore local knowledge related to chemical reactions and incorporate it into science classroom practices. It was based on the qualitative method with an interpretative phenomenological design. The unstructured interviews with three science teachers of Kathmandu Valley, who have more than 15 years of teaching experience in science teaching, were involved in the interview as participants. The interviews were transcribed, coded, and themes were constructed through the categorization of codes. Thematic analysis is employed to identify key insights and patterns. The findings reveal that integrating local practices enhances science education through culturally relevant teaching methods and fostering deeper student engagement.